VD_FINDINFO Jug-inc / 2009 / 24 vom 29. September 2009 - VD Tribunal cantonal (2009)
CONSORITÉ, CONNEXITÉ MATÉRIELLE, COMPÉTENCE RATIONE LOCI, DÉCISION INCIDENTE | 147 CPC, 149 al. 4 CPC, 17 CPC, 19 CPC, 56 CPC, 57 CPC, 58 CPC, 59 CPC, 19 al. 1 let. c LFors, 19 LFors, 7 al. 1 LFors